Neurophysiological Characterization of Subacute Stroke Patients: A Longitudinal Study - Lamola, Giuseppe; Fanciullacci, Chiara; Sgherri, Giada; Bertolucci, Federica; Panarese, Alessandro; Micera, Silvestro; Rossi, Bruno; Chisari, Carmelo (Frontiers in Human Neuroscience, 2016)
Various degrees of neural reorganization may occur in affected and unaffected hemispheres in the early phase after stroke and several months later. Recent literature suggests to apply a stratification based on lesion location and to consider patients with cortico-subcortical and subcortical strokes separately: different lesion location may also influence therapeutic response. In this study we used a longitudinal approach to perform TMS assessment (Motor Evoked Potentials, MEP, and Silent Period, SP) and clinical evaluations (Barthel Index, Fugl-Meyer Assessment for upper limb motor function and Wolf Motor Function Test) in 10 cortical-subcortical and 10 subcortical ischemic stroke patients. Evaluations were performed in a window between 10 and 45 days (t0) and at 3 months after the acute event (t1). Our main finding is that 3 months after the acute event patients affected by subcortical stroke presented a reduction in contralateral SP duration in the unaffected hemisphere; this trend is related to clinical improvement of upper limb motor function. In conclusion, SP proved to be a valid parameter to characterize cortical reorganization patterns in stroke survivors and provided useful information about motor recovery within three months in subcortical patients.